TINJAUAN GEOGRAFIS TERHADAP UPAYA PENGEMBANGAN AGROWISATA SAWAH SOLOK DI KECAMATAN LUBUK SIKARAH KOTA SOLOK - RANNY PERMATA SARI; Ratna Wilis (JURNAL BUANA, 2019)
This research is located in Kelurahan IX Korong, Lubuk Sikarah District, Solok City. The purpose of this study is to determine the geographical factors that can support in the development of agro-tourism. The benefits of this research are (1) being one of the meaningful inputs for the people of Solok City and the local government in particular, (2) it can be used for further research, (3) it is hoped that this research will be an input for developing Solok Rice Field Agrotourism into an attractive tourist area to visit. For the population in this study are Sawah Solok Agrotourism, Sawah in Sinapa Piliang Village, and Sawah in KTK Village. The method used in the study is the documentation method, questionnaire method, observation method, and interview method. Analysis of the data used in this study is a qualitative descriptive analysis and scoring analysis. From the results of the research that has been carried out it can be seen that the four aspects namely physical, social and cultural aspects, facilities, and accessibility play an important role in the effort to develop agro-tourism. So that we can see the extent to which agro-tourism has developed and what needs to be added or improved in the agro-tourism area. Based on the results of the study, Sawah Solok agrotourism has the potential to be developed as an agro-tourism area viewed from the four aspects. However, the paddy fields in Sinapa Piliang Village and the paddy fields in the KTK Kelurahan only support the physical aspects, but not the other three aspects. Keywords: Agrotourism, geographical overview, agro-tourism development